Mainstreaming health and wellness: The RHWP Innovation model to complement primary care. Issue 2 (29th January 2019) - Parsons, Pamela L.; Slattum, Patricia W.; Bleich, Michael
Abstract: Problem statement: Multiple chronic conditions combined with the complex social needs of individuals and families often create unattainable goals of efficient and effective holistic care within primary care settings. There is a recognized need for new approaches to address the intersection of the role of social determinants of health and the resulting impact on health care utilization and outcomes as an approach to enhancing value‐based care. Model description: This paper describes an innovative health and wellness model that complements the essential work of primary care providers (PCPs), as an adjunct to care delivery. The wellness program helps meet unrealistic expectations placed on providers to cover a full range of holistic services while reducing the burden on under‐ or uninsured patients to seek timely care. The model describes an academic‐community based partnership that integrates student learning into the delivery of a wellness program provided on‐site to adults residing in apartment buildings designated for low‐income and disabled adults. The innovation described is a health and wellness model that complements the demands placed on primary care clinics.